Faktor-Faktor Yang Mempengaruhi Terjadinya Fraud Di Sektor Pemerintahan (Studi Empiris Pada Pemerintah Kabupaten Biak Numfor) - Galih J. M Mansnandifu; Mariolin Ance Sanggenafa; Rudiawie Larasati (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
This study aims to determine the effect of compensation suitability, the effectiveness of internal control and organizational culture on fraud in the Biak Numfor Regency Regional Government Agencies. The data of this study were obtained from questionnaire data (primary). The population in this study are all employees who work in the finance sub-section in each Regional Government Agency of Biak Numfor Regency. The sampling method was purposive sampling, obtained 105 samples. This study uses a quantitative approach. The analysis used is multiple linear analysis, with t-test and coefficient of determination. The test results show that, firstly, the suitability of compensation has a significant effect on fraud. Second, the effectiveness of internal control has a significant effect on fraud. The three organizational cultures have no significant effect on fraud. The coefficient of determination is 0.309 or 30.9%, which means that the amount of compensation, the effectiveness of internal control and organizational culture against fraud is 30.9%, while the remaining 69.1% is explained by other causes originating from outside the regression that are not investigated in this study.